1996
DOI: 10.1152/ajprenal.1996.271.4.f861
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of epithelial Na+ channels from M-1 cortical collecting duct cells

Abstract: The M-1 cell line is derived from the mouse cortical collecting duct and displays the low-conductance, highly Na(+)-selective channel activity of the alpha,beta, gamma-heterotrimeric epithelial Na+ channel (ENaC). The short-circuit current (Isc) across M-1 monolayers was 89 +/- 4 microA/cm2, and the transepithelial conductance was 2.1 +/- 0.2 mS/cm2. Isc was abolished by blocking the Na+ pump with ouabain. Both Isc and transepithelial conductance (gT) were inhibited by benzamil > amiloride >> dimethylamiloride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…These minor discrepancies may be the result of batch-to-batch variability in oocytes, which we have tried to account for by normalizing our data, as well as the potentially nonlinear nature of the chemiluminescence surface expression assay compared with TEV. These data do not rule out alterations in mENaC P o or unitary conductance, but subtle changes in P o can be difficult to ascertain because P o can vary widely in ENaC (32).…”
Section: Discussionmentioning
confidence: 89%
“…These minor discrepancies may be the result of batch-to-batch variability in oocytes, which we have tried to account for by normalizing our data, as well as the potentially nonlinear nature of the chemiluminescence surface expression assay compared with TEV. These data do not rule out alterations in mENaC P o or unitary conductance, but subtle changes in P o can be difficult to ascertain because P o can vary widely in ENaC (32).…”
Section: Discussionmentioning
confidence: 89%
“…M-1 cells, which preserve functional properties typical for cortical collecting duct principal cells in vivo, reabsorb sodium and secrete potassium through a corticosteroid regulated Na + channel (Chalfant et al, 1996). Recent studies have demonstrated that dexamethasone stimulates Na + transport in M-1 cells (Nakhoul et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…1D) and the lack of change in oocyte capacitance in response to Ni 2ϩ (31). The open probability of ENaC has been shown to be highly variable in different systems (1,95 binding leads to a decrease in ENaC P o , based on our presumption that the Ni 2ϩ -binding site is located within the extracellular region outside of the conduction pore. One model (the "gate" model) places the Ni 2ϩ -binding site within a putative gate that swings into the outer vestibule of the pore during channel closure.…”
mentioning
confidence: 95%